Parallelizing the Training of the Kinect Body Parts Labeling Algorithm - Budiu, Mihai; Shotton, Jamie; Murray, Derek; Finocchio, Mark (BigLearn Workshop at NIPS, 2011)
We present the parallelized implementation of decision forest training as used in Kinect to train the body parts classification system. We describe the practical details of dealing with large training sets and deep trees, and describe how to parallelize over multiple dimensions of the problem.